The effect of individual and organizational related factors that support career development towards employees’ career satisfaction - Siti Mariam, Sulaiman; Dayang Kartini, Abang Ibrahim; Victoria, Jonathan (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Over the past several years, a number of researchers have examined employees’ career success which paying particular attention to the individual and organizational factors that have impact on the construct of their employees’ career satisfaction. This study examined the effect of individual and organizational related factors that support career development towards employees’ career satisfaction. A 40-item questionnaire was constructed and administered to 158 respondents in government sectors. The analytical procedure of Pearson Correlation Analysis was utilized to determine the predicting strength among career satisfaction and the independent variables. Pearson Correlation Analysis revealed that positive correlation existed between the independent variables (perceived organizational support, organizational learning culture, empowerment and career management behavior) and dependent variable (employees’ career satisfaction). This study provides new support to previous research about the individual and organizational related factors that support career development which enable to enhance employees’ career satisfaction especially in government sector. Reasons for these findings are discussed.